2012
DOI: 10.1097/ico.0b013e3182254b78
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Basement Membrane Composition of the Human Limbus Epithelium and Amniotic Membrane Epithelium

Abstract: Despite extensive similarities in basement membrane composition between amniotic and corneolimbal epithelia, the lack of limbus-specific environmental factors argues against the potential of denuded amniotic membrane as a surrogate niche for limbal stem cells but supports its suitability as a substrate to promote the formation of a well-differentiated stratified corneal epithelial equivalent for tissue engineering strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 40 publications
0
22
0
1
Order By: Relevance
“…As described above, several labs have demonstrated perlecan’s presence in the basement membrane of the normal corneal epithelium (Dietrich-Ntoukas et al, 2012; Schlötzer-Schrehardt et al, 2007), separating the epithelial and stromal layers, and in Descemet’s membrane, separating the stromal and endothelial layers. Its expression varies with age (Kabosova et al, 2007), and across various locations (Ljubimov et al, 1995), and is known to be expressed by corneal stromal cells, both normally and in response to injury (Brown et al, 1999; Hassell et al, 1992).…”
Section: Loss Of Perlecan At Tissue Borders Associated With Patholmentioning
confidence: 89%
See 1 more Smart Citation
“…As described above, several labs have demonstrated perlecan’s presence in the basement membrane of the normal corneal epithelium (Dietrich-Ntoukas et al, 2012; Schlötzer-Schrehardt et al, 2007), separating the epithelial and stromal layers, and in Descemet’s membrane, separating the stromal and endothelial layers. Its expression varies with age (Kabosova et al, 2007), and across various locations (Ljubimov et al, 1995), and is known to be expressed by corneal stromal cells, both normally and in response to injury (Brown et al, 1999; Hassell et al, 1992).…”
Section: Loss Of Perlecan At Tissue Borders Associated With Patholmentioning
confidence: 89%
“…Researchers may instinctively employ biologically-derived substrates to support cell proliferation and organization. For example, amniotic membrane is frequently employed, as it contains many basement membrane components, can be easily harvested and preserved, and may be sufficiently anti-inflammatory and anti-immunogenic for this use (Ahn et al, 2007; Dietrich-Ntoukas et al, 2012). However, the chief disadvantage of such biologically-derived membranes is their inherent variability, which may vary with the site of harvest, the age of the donor, post-processing methods, and the duration of pregnancy at the time of harvest.…”
Section: Translating Boundary Functions Into Useful Constructs Formentioning
confidence: 99%
“…This is because the amniotic membrane is a soft semitransparent membrane without the corneal unique histoarchitecture. 31 Recent studies showed that a collagen scaffold constructed with porcine collagen was well-tolerated after heterogeneous implantation, and the porcine cornea shared similar anatomic characteristics with the human cornea. [32][33][34] Our previous research also indicated that the acellular porcine cornea matrix, which was developed by 0.5% sodium dodecyl sulfate (SDS) could preserve the key features of the cornea, including the intact basement membrane, and support the growth of CECs and keratocytes in vitro.…”
Section: Introductionmentioning
confidence: 98%
“…To confirm that the lack of tyrosine sulfate recognition by PSG2 of the TM clone was due to the fact that only three tyrosine sulfate residues (192, 196, and 198) existed in Fbln2, all independent mutant clones along with WT and vector were transiently transfected into HEK293T, and cells were grown in the presence of Na 2 35 SO 4 . Media from these clones were immunoprecipitated with an anti-Myc antibody.…”
Section: Journal Of Biological Chemistry 13425mentioning
confidence: 99%
“…Fibulins are members of a seven-member family of extracellular matrix (ECM) 3 proteins that are important constituents of elastic fibers and basement membranes (1)(2)(3)(4)(5). They are divided into two classes based on their size (6).…”
mentioning
confidence: 99%